The Role of Library and The Library of Special Needs School Staff in Implementation of The School Literacy Movement (Gls) for Visually Impaired Student - Karrany, Zahra Nurfabella; Saepudin, Encang; Prahatmaja, Nurmaya (Edulib, 2023)
This research aims to determine the implementation of Gerakan Literasi Sekolah and the role of libraries and library staffs of extraordinary school in implementing Gerakan Literasi Sekolah for Visually Impaired Students at SLBN-A Citeureup Kota Cimahi referring to the Minister of Education and Culture Regulation No. 23 of 2015 concerning manners. The research method used in this study is a qualitative research method with a case study approach. Data collection techniques were carried out through observation, interviews, literature studies and documentation. The results of this study indicate that (1) the role of the library of extraordinary school in the implementation of GLS at SLBN-A Citeureup is to provide facilities and infrastructure for residents in the school environment to carry out literacy by procuring a collection of books, CDs, tools for literacy and placing reading corners at strategic places. (3) the role of library staff in implementing GLS at SLBN-A Citeureup is to become a facilitator in carrying out GLS program policies and preparing everything related to the needs of GLS activities in schools